2018
DOI: 10.1002/jhet.3110
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and In Vitro Anticancer Activity of Novel 1,3,4‐Oxadiazole‐Linked 1,2,3‐Triazole/Isoxazole Hybrids

Abstract: A series of new 1,3,4‐oxadiazole‐linked 1,2,3‐triazole/isoxazole derivatives were designed and synthesized. All the synthesized compounds were screened for in vitro anticancer activity against four human cancer cells: HeLa (cervical), MDA‐MB‐231 (breast), DU‐145 (prostate), and HEPG2 (liver). Among 17 compounds tested, 7a, 7c, and 7d showed potent activity toward four cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Individually, 1,3,4-oxadiazole and 1,2,3-triazole moieties are of significant biological interest owing to their importance in drugs and pharmaceuticals. A series of new 1,3,4-oxadiazole-linked 1,2,3-triazole derivatives were reported by Madhavilatha et al (2018).Compounds tested, 3-((1-Benzyl-1H-1,2,3-triazol-4-yl)methyl)-5-phenyl-1,3,4oxadiazol-2(3H)-one (42), 3-((1-Benzyl-1H-1,2,3-triazol-4-yl)methyl)-5-(p-tolyl)-1,3,4-oxadiazol-2(3H)-one (43), and 3-((1-(2-Fluorobenzyl)-1H-1,2,3-triazol-4-yl)methyl)-5-(ptolyl)-1,3,4-oxadiazol-2(3H)-one (44) showed utmost anticancer activity against HeLa (cervical), MDA-MB-231 (breast), DU-145 (prostate), and HEPG2 (liver) cancer cell lines (Figure 18). Western blot analysis in the HeLa cell line indicated that these compounds induced cyclin B1 protein level, which is a strong indicator of G2/M cell cycle arrest and disrupted microtubule assembly and increased the amount of insoluble tubulin fractions of cells like other potent tubulin polymerization inhibitors such as nocodazole.…”
Section: 34-oxadiazolesmentioning
confidence: 99%
“…Individually, 1,3,4-oxadiazole and 1,2,3-triazole moieties are of significant biological interest owing to their importance in drugs and pharmaceuticals. A series of new 1,3,4-oxadiazole-linked 1,2,3-triazole derivatives were reported by Madhavilatha et al (2018).Compounds tested, 3-((1-Benzyl-1H-1,2,3-triazol-4-yl)methyl)-5-phenyl-1,3,4oxadiazol-2(3H)-one (42), 3-((1-Benzyl-1H-1,2,3-triazol-4-yl)methyl)-5-(p-tolyl)-1,3,4-oxadiazol-2(3H)-one (43), and 3-((1-(2-Fluorobenzyl)-1H-1,2,3-triazol-4-yl)methyl)-5-(ptolyl)-1,3,4-oxadiazol-2(3H)-one (44) showed utmost anticancer activity against HeLa (cervical), MDA-MB-231 (breast), DU-145 (prostate), and HEPG2 (liver) cancer cell lines (Figure 18). Western blot analysis in the HeLa cell line indicated that these compounds induced cyclin B1 protein level, which is a strong indicator of G2/M cell cycle arrest and disrupted microtubule assembly and increased the amount of insoluble tubulin fractions of cells like other potent tubulin polymerization inhibitors such as nocodazole.…”
Section: 34-oxadiazolesmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Among different triazoles, 1,2,3triazoles particularly have a broad range of applications in the field of pharmaceutical and medicinal chemistry, and they are a part of many molecules reported as antidiabetic. [17][18][19][20][21][22][23][24] It has been reported that benzimidazole compounds, that is, 2-aryl benzimidazoles (A) and 2-(2chlorophenyl)-7-methyl-1H-benzo [d]imidazole (B), act as α-glucosidase inhibitors, [25][26][27] but there is still a need to discover some new analogs for improved inhibitory activity. Various studies have reported that by combining a benzimidazole ring with an electron-withdrawing group such as triazole, the biological activity gets enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…However, 1,3,4‐oxadiazol‐2(3 H )‐one (Fig. ) is a privileged five‐membered heterocycle and has a revitalized interest due to its broad pharmaceutical scope encompassing activities such as anti‐tumor, HCV , anti‐cancer [18a], protoporphyrinogen (PPO) inhibitors as commercial herbicides [18b], hormone‐sensitive lipase , antibacterial , antitubercular , GABA receptor agonists [22a], anti‐microbial [22b], and inhibition of selective monoamine oxidase B . BemPPOX is an oxadiazolone inhibitor slowing down fat digestion, absorption, and targeting selectively gastric lipolysis .…”
Section: Introductionmentioning
confidence: 99%